PICIGIN: LANGUAGE OF A GAME AND A GAME OF LANGUAGE (Philological Studies, 2023)
The paper presents the results of field research of intragroup communication and language practices of members of one of the most recognizable Split subcultures – picigin players. The fundamental research question is whether a specific intra-group code was created within the urban vernacular of the city of Split under conditions of long-term intensive contact in a predominantly male circle – in the form of a special sociolect or only a communicative style, i.e. in what way language practice contributes to the formation of the identity of the researched group. The material collected by surveying and interviewing members of this community is analyzed from a narrower linguistic aspect, but also interpreted in a broader (socio)linguistic context. The collected language units with broader intra-group usage, mainly lexemes and idioms, including onymes, are categorized in terms of meaning, and the most frequent word formation processes and associated metaphorical concepts are specified as well. The paper also discusses the attitudes of picigin players towards different language varieties of the city of Split, as well as some gender aspects of their intragroup communication and the role of humor in shaping and expressing their social identity.